2020
DOI: 10.1051/e3sconf/202019602027
|View full text |Cite
|
Sign up to set email alerts
|

Research of the process of radon accumulation in the accumulating chamber taking into account the nonlinearity of its entrance

Abstract: The paper presents a mathematical model of radon accumulation in a chamber, which takes into account the hereditary properties of the environment in which radon migrates, and also uses a nonlinear function that is responsible for the mechanisms of radon entering the chamber. The simulation of accumulation is performed in comparison with real data. It is shown that the model presented in this work gives a better agreement between the model and real curves of radon accumulation and can be used for a more accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It can be concluded that an explicit finite-difference scheme can be used to calculate dynamic processes in environments with saturation. Further continuation of the work lies is the practical application of an explicit finite-difference scheme for calculating the curves of the volumetric activity of radon in a storage chamber by analogy with work [36].…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that an explicit finite-difference scheme can be used to calculate dynamic processes in environments with saturation. Further continuation of the work lies is the practical application of an explicit finite-difference scheme for calculating the curves of the volumetric activity of radon in a storage chamber by analogy with work [36].…”
Section: Discussionmentioning
confidence: 99%